Melanoma of the central nervous system based on neurocutaneous melanocytosis in childhood: a rare but fatal condition - Abele, Michael; Forchhammer, Stephan; Eigentler, Thomas K.; Popescu, Aryana; Maschke, Linda; Lohse, Judith; Lehrnbecher, Thomas; Behnisch, Wolfgang; Groll, Andreas H.; Jakob, Marcus; Bernbeck, Benedikt; Brecht, Ines B.; et al. (Pediatric blood & cancer, 2024)
Background: Melanomas of the central nervous system (CNS) based on neurocutaneous melanocytosis (NCM) are exceptionally rare in childhood and have been described only sporadically. Rapidly progressive disease may represent a major challenge for treating physicians, especially given the limited knowledge about this condition. This analysis aimed to increase knowledge about the occurrence and treatment of these malignancies. Procedure: Data on diagnosis, treatment, and outcome of patients aged 0-18 years with CNS melanoma based on NCM recorded in the German Registry for Rare Pediatric Tumors (STEP registry) were analyzed. Additionally, published case reports on this condition were analyzed. Results: In STEP, five patients with leptomeningeal melanoma based on NCM were identified, with a median age at melanoma diagnosis of 3.7 years. Various multimodal treatments were performed: (partial) resection (n = 4), irradiation (n = 2), trametinib (n = 3), different cytostatics (n = 2), and anti-GD2 immunotherapy (n = 1). All patients died between 0.3 and 0.8 years after diagnosis. Including published case reports, 27 patients were identified with a median age of 2.8 years at melanoma diagnosis (range: 0.2-16.6). Fourteen of 16 cases with reported data had a NRAS alteration (88%), particularly NRAS p.Q61K (85%). In the expanded cohort, no patient survived longer than 1 year after diagnosis despite multimodal therapy (including trametinib; n = 9), with a median survival of 0.4 years (range 0.1-0.9). Conclusions: CNS melanomas based on NCM in childhood are aggressive malignancies without curative treatment to date. Therapeutic approaches must be individualized. Genetic tumor sequencing is essential to improve understanding of tumorigenesis and potentially identify new therapeutic targets.